2016
DOI: 10.1021/acs.jpclett.6b00720
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Single-Molecule Fluorescence Correlation Spectroscopy Enables Kinetics Study of DNA Hairpin Folding with a Time Window from Microseconds to Seconds

Abstract: Single-molecule fluorescence measurements have been widely used to explore kinetics and dynamics of biological systems. Among them, single-molecule imaging (SMI) is good at tracking processes slower than tens of milliseconds, whereas fluorescence correlation spectroscopy (FCS) is good at probing processes faster than submilliseconds. However, there is still shortage of simple yet effective single-molecule fluorescence method to cover the time-scale between submilliseconds and tens of milliseconds. To effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 39 publications
3
37
0
Order By: Relevance
“…This indicates that the reaction rate constants do not depend strongly on the structure of the oligonucleotide and that the fluorescent molecules are not protected from solvent in the duplex (Figure b). This result is consistent with previous studies that indicated that rhodamine did not stack with the duplex . As k ss / k ds is slightly smaller than unity, the reaction of the fluorescent molecule and oxidant is faster in the double‐stranded than in the single stranded oligonucleotide.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This indicates that the reaction rate constants do not depend strongly on the structure of the oligonucleotide and that the fluorescent molecules are not protected from solvent in the duplex (Figure b). This result is consistent with previous studies that indicated that rhodamine did not stack with the duplex . As k ss / k ds is slightly smaller than unity, the reaction of the fluorescent molecule and oxidant is faster in the double‐stranded than in the single stranded oligonucleotide.…”
Section: Resultssupporting
confidence: 92%
“…This result is consistent with previous studies that indicated that rhodamine did not stack with the duplex. [52] As k ss /k ds is slightly smaller than unity,t he reaction of the fluorescent molecule and oxidant is faster in the double-stranded than in the single stranded oligonucleotide. The fluctuating conformation of the single strand may slightly inhibit the oxidantf rom approachingt he fluorescent molecule.…”
Section: Discrimination Betweens Ingle-strandedand Double-stranded Stmentioning
confidence: 99%
“…[31] This difference between R6G and ATTO 655 may stem from incomplete stacking of rhodamine dyes in the context of ad uplex structures,a ss uggested in previous studies. [33,46] This is in line with our previous report that the nature of the fluorophore used is critically important for sensitive read-out of the microenvironment around the fluorophore in rKACB. [31] To investigate whether rKACB is effective at monitoring the conformational switching dynamics of nucleic acids,w e performed real-time single-molecule analysis of conformational switching of the preQ 1 riboswitch from Fusobacterium nucleatum mRNA.…”
Section: Angewandte Chemiesupporting
confidence: 89%
“…To nd out whether the single FRET peak represents a single half-open state or is due to the fast interchange between the open and closed states, we conducted the FRET-FCS experiment on a home-built scanning confocal microscope. 16 No dynamic relaxation process was observed in 90-210_F-DNA Me (Fig. S10 †), conrming that the FRET peak signals a single half-open state.…”
mentioning
confidence: 99%